2002
DOI: 10.1002/cncr.10489
|View full text |Cite
|
Sign up to set email alerts
|

CD56+ TdT+ blastic natural killer cell tumor of the skin

Abstract: BACKGROUNDAn unusual cutaneous tumor that has blastic morphology and coexpresses CD56 and terminal deoxynucleotidyl transferase (TdT) has been recently recognized and termed blastic natural killer cell lymphoma.METHODSThe authors identified seven cases of such CD56+TdT+ blastic tumors presenting in skin at their institution. The authors correlated clinical course with histomorphology and immunophenotype.RESULTSAll 7 patients (6 men, 1 woman, 52‐85 years) presented with rapidly growing, frequently multiple cuta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(21 citation statements)
references
References 18 publications
3
18
0
Order By: Relevance
“…In the literature, we found only four cases that could be considered CD4-negative variants of genuine HN. [9][10][11] Similar to our cases, these cases showed some phenotypic variability, underlying the necessity for a large panel of antibodies in the diagnosis of HN. In fact, the two cases of HN described by Bekkenk et al 10 were positive for TdT and also expressed some T-cell markers (one case was CD81 and CD52/1, and the second was CD21).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In the literature, we found only four cases that could be considered CD4-negative variants of genuine HN. [9][10][11] Similar to our cases, these cases showed some phenotypic variability, underlying the necessity for a large panel of antibodies in the diagnosis of HN. In fact, the two cases of HN described by Bekkenk et al 10 were positive for TdT and also expressed some T-cell markers (one case was CD81 and CD52/1, and the second was CD21).…”
Section: Discussionsupporting
confidence: 82%
“…On the other hand, cases of HN with ambiguous phenotype could represent examples of blastic tumors with mixed precursor plasmacytoid dendritic and myelomonocytic features, possibly representing a spectrum of precursor hematologic neoplasms. This hypothesis is supported by the evidence that patients with HN can develop AML during the course of the disease 9,15 or can present at diagnosis with a concurrent myeloproliferative disorder. 4 In addition, phenotypic overlaps with cAML have been reported, as some cases of cAML can express CD123 and/or TCL1.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Although several lines of evidence regarding the ontogenic origin of plasmacytoid DC suggest a lymphoid origin [5,7,16], other findings have indicated that plasmacytoid DC are related to a myeloid lineage. For example, the transdifferentiation of BPDCN into chronic myelomonocytic leukemia or acute myeloid leukemia has been reported in some cases [17,18]. Interestingly, it has been demonstrated that both common myeloid progenitors and common lymphoid progenitors are able to generate interferon-producing plasmacytoid DC that are able to activate lymphoid-specific genetic programs [19].…”
Section: Discussionmentioning
confidence: 99%
“…Since pDC-characteristic surface phenotypes were not evaluated in leukemic blasts of M4 acute leukemia, it is difficult to say whether or not M4 leukemia and pDCL derived from the common precursor cells in the pDC lineage. However, an association of myelodysplasia with pDCL or a history of myelodysplastic syndrome before pDCL has been reported previously [13, 36, 37]. These reports may suggest a close relationship between M4 acute leukemia and pDCL in case 2.…”
Section: Discussionmentioning
confidence: 56%